Utilization Pattern of Power sources on Productivity of Groundnut and Cotton Dryland Production Systems - Reddy, B Sanjeeva; Adake, R V; Thyagaraj, C R; Reddy, K Srinivas (Journal of Agricultural Engineering, 2009)
A field study was conducted in groundnut and cotton production systems under dry farming conditions to assess the utilization of different power sources and energy use pattern. Ninety farms were studied using a structured questionnaire. The mechanization in the groundnut system in Anantapur was observed to be higher than the other dry farming production systems. The mean annual working hour of tractors in groundnut and cotton production system was 1,015 and 1,080 hours, respectively. The tractors owned were used for custom hiring for 58 and 69 % of annual usage in groundnut and cotton based production systems, respectively. The total energy used in rain fed groundnut production system was in the range of 4,299 to 9,572 MJ/ha and rain fed cotton system was 7,240 to 10,724 MJ/ha. Small and marginal resource poor farmers were unable to make proper investment to increase the crop productivity. Interventions like custom hiring centres managed by local community and cooperative farming at cluster level could ensure increased use of farm machinery, reducing farm drudgery.